Health Awareness Among Waterpipe Smokers in Sulaimani City/Iraq: Anticipation of Hazardous Impacts and Attitudes Towards Nicotine Replacement Therapy - Hozan Hama Salh; Dlivan Aziz; Kawa Obeid (المجلة العراقية للصيدلة, 2024)
Background: Over the past decade, the number of waterpipe smokers in Iraqi Kurdistan Region has increased. The driven factors behind this surge, as well as the extent of knowledge about its medical ramifications has not been fully elucidated among its users in this region. Therefore, this study was designed to evaluate the prevalence of waterpipe smokers in the Sulaimani city/Iraq and to investigate the knowledge and attitude towards this habit along with methods of evading this habit. Method: This cross-sectional study was carried out from July 2022 to August 2022 in Sulaimani/Iraq. One hundred eighty-one waterpipe smokers participated in the study. Various aspects have been addressed using questionnaires including behaviors, perception and knowledge towards waterpipe smoking (WPS). Moreover, personal awareness regarding nicotine replacement therapy (NRT) were addressed. Data analysis was performed using Graphpad Prism 7. Results: Results have shown that significant number of participants (79.6%) are waterpipe smoking in the cafes while huge number of them (57.5%) have not any family members smoking WP. Results also revealed that 86.2 % of participants are male and they mainly single. Most of the participants are aware of the health risks of their smoking behaviors. While, majority of them have not heard about NRT. Despite the awareness of its ramifications, 19.9 % of participants suffered harm from using waterpipe smoking. Conclusion: In conclusion, most of our participants had the good perception that waterpipe smoking has health problems. However, there is no information regarding the method of using NRT. Resulting efforts are needed to further raise the public awareness about the impacts of WPS, and they should be guided towards behavioural changes and using NRT as an alternative method.